Depressive symptoms mediate the association between sleep disorders and gallstone disease: a causal mediation analysis of NHANES 2017–2020 - Hou, Yisen; Li, Rui; Xu, Zhen; Chen, Wenhao; Li, Zhiwen; Jiang, Weirong; Meng, Yong; Han, Jianli (Frontiers in Psychiatry, 2025)
BackgroundGallstones are a prevalent digestive system disorder with significant health implications. Recent research suggests that sleep disorders, such as insomnia and obstructive sleep apnea hypopnea syndrome, may influence the development of gallstones through various metabolic pathways. Depression, often accompanying sleep disorders, may play a mediating role in this relationship. This study uses data from the 2017–2020 National Health and Nutrition Examination Survey (NHANES) to explore the potential mediating role of depression in the association between sleep disorders and gallstones.MethodsWe analyzed data from 7,868 adults aged 20 and older from NHANES 2017–2020. Gallstones were defined based on self-reported medical diagnoses. Sleep disorders were assessed through self-reported sleep difficulties, and depressive symptoms were measured using the Patient Health Questionnaire-9 (PHQ-9) scale. Logistic regression models evaluated direct associations between sleep disorders, depressive symptoms, and gallstones. Causal mediation analysis further examined the mediating role of depressive symptoms. Finally, subgroup analyses were performed by age, sex, and obesity status.ResultsBoth sleep disorders (OR = 2.00; 95% CI, 1.73-2.32; P<0.001) and depressive symptoms (OR = 2.09; 95% CI, 1.70-2.56; P<0.001) were significantly associated with gallstones, with results remaining significant after adjusting for confounders. A significant association was also observed between sleep disorders and depressive symptoms (OR = 5.53; 95% CI, 4.71-6.50; P<0.001). Mediation analysis indicated that depressive symptoms partially mediate the relationship between sleep disorders and gallstones, with an average causal mediation effect (ACME) of 0.00720 (95% CI, 0.00299-0.01220; P<0.001) and an average direct effect (ADE) of 0.0305 (95% CI, 0.0129-0.0488; P<0.001). Depression mediates 18.89% (95% CI, 0.0704-0.4096; P<0.001) of the association between sleep disorders and gallstones. Subgroup analyses showed significant mediation by depressive symptoms in individuals aged 40-59, males, and both obese and non-obese groups (all P<0.05), although no significant mediation was found in females (P>0.05).ConclusionThis study demonstrates a significant association between sleep disorders and gallstones, with depressive symptoms playing a partial mediating role. Improving depressive symptoms may help reduce the risk of gallstones associated with sleep disorders.